Association of muscle fiber composition with health and exercise-related traits in athletes and untrained subjects - C. R. Hall, Elliott; Semenova, Ekaterina; Bondareva, Elvira A.; Borisov, Oleg; Andryushchenko, Oleg N.; Andryushchenko, Liliya; Zmijewski, Piotr; Generozov, Edward; Ahmetov, Ildus (Biology of Sport, 2021)
Skeletal muscle is a heterogenous and metabolically active tissue, the composition of which is associated with multiple traits. The aim of the study was to determine whether there are additional health and exercise-related traits associated with muscle fiber composition in athletes and non-athletes. This study recruited 164 Russian participants (51 endurance and 48 power athletes; 65 controls). Vastus lateralis muscle fiber composition was assessed by immunohistochemistry. Slow-twitch muscle fiber percentage (STMF%) was significantly greater in endurance than power athletes and non-athletes, and in non-athlete females than males. STMF% was positively associated with athletes’ training frequency, non-athletes’ and endurance athletes’ age, endurance athletes’ competition level and chest depth, and power athletes’ training age. STMF% was negatively associated with diastolic blood pressure in power athletes and with systolic blood pressure and reaction time in non-athletes. In all participants, STMF% was positively associated with age, tolerance to long distance exercise, chest depth and fracture incidence, and negatively with systolic blood pressure and resting heart rate. Age, sex and training frequency explained 10.6% and 13.2% of the variance in STMF% in endurance and power athletes, respectively. This is one of the most comprehensive studies involving athletes and untrained subjects and provides novel information concerning associations of increased STMF percentage with lower resting heart rate, better tolerance to long distances, faster reaction time and larger chest depth. On the other hand, the increased percentage of fast-twitch muscle fibers was associated with rare fracture incidence.